Optimalisasi Pelatihan Ekonomi Kreatif Dalam Pengelolaan UMKM Laskar Bima Craft Di STIT Sunan Giri Bima - Diki candra; Fitri Wulandari (Rayah Al-Islam, 2025)
This study aims to strengthen the capabilities of micro, small, and medium enterprises (MSMEs) with an approach focused on the creative economy. This research is important because MSME are the foundation of the local economy, but often experience difficulties such as lack of innovation, inefficient management, and limited access to markets. Through descriptive qualitative research methods, data obtained from observations, in-depth interviews, and innovative marketing strategies can significantly increase the competitiveness of Laskar Bima Craft. The novelty of this study lies in creative economy training with higher education based on local wisdom and the development of students' soft skills as agents of change, while the implications include strengthening the local creative economy ecosystem, as well as increasing the role of Laskar Bima Craft MSME managers to reach 80% sustainability.